2013
DOI: 10.1002/jat.2928
|View full text |Cite
|
Sign up to set email alerts
|

Towards an integrated in vitro strategy for estrogenicity testing

Abstract: In order to define an in vitro integrated testing strategy (ITS) for estrogenicity, a set of 23 reference compounds representing diverse chemical classes were tested in a series of in vitro assays including proliferation and reporter gene assays. Outcomes of these assays were combined with published results for estrogen receptor (ER) binding assays and the OECD validated BG1Luc ER transcriptional activation (TA) assay and compared with the outcomes of the in vivo uterotrophic assay to investigate which assays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 45 publications
1
34
0
1
Order By: Relevance
“…The proliferation assay detects estrogenic activity by measuring an increase in proliferation of MCF-7/BOS cells which is mediated via ERs (Desaulniers et al 1998 ; Wang et al 2012 ; Zacharewski 1997 ). Data of E2 and BPA in these in vitro assays were obtained from different studies from the literature (Kolle et al 2010 ; Wang et al 2012 , 2014 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The proliferation assay detects estrogenic activity by measuring an increase in proliferation of MCF-7/BOS cells which is mediated via ERs (Desaulniers et al 1998 ; Wang et al 2012 ; Zacharewski 1997 ). Data of E2 and BPA in these in vitro assays were obtained from different studies from the literature (Kolle et al 2010 ; Wang et al 2012 , 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Concentration–response data for E2 and BPA can be derived from a wide range of in vitro estrogenicity assays, including the MCF-7/BOS proliferation assay, the U2OS estrogen receptor-mediated chemical-activated luciferase gene expression (ER-CALUX) assay and the yeast estrogen screen (YES) assay. A previous study showed that the in vitro proliferation assay and reporter gene assays (ER-CALUX and YES assay) showed a reasonably good correlation with the in vivo uterotrophic assay (Wang et al 2014 ). However, this analysis was performed without taking the kinetics into consideration and did not provide points of departure that can be used in risk assessment.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Only 5 new toxicological mechanistic studies were found. Two of them confirm estrogenicity of chlordecone and were more designed to develop new estrogenic tests [ 129 , 130 ]. One study shows how chlordecone among others regulates the liver drug transporter activity and expression [ 131 ]; that may contribute to the liver toxicity that we have already taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Ensaio de gene repórter cuja ligação depende de atividade de transcrição e tradução Estes ensaios analisam não apenas a capacidade do composto de se ligar ao receptor, mas também de expressar resposta. Os hormônios ligam-se aos receptores, atingem o núcleo das células, interagem com o elemento respondedor a estrógeno do gene alvo e transcrevem o mecanismo de ação (ROTROFFSHEN et al, 2013;SOTO et al, 2006;WANG et al, 2013).Os bioensaios anteriormente descritos foram comparados porLeusch et al (2010), que concluíram que o teste de maior sensibilidade foi o ER-Calux (Estrogen Receptor Chemical Activated Luciferase Gene eXpression). O ensaio utiliza células humanas de câncer de mama com receptores alfa e beta (ERα e ERβ), que são mediados pelo gene repórter que contém três elementos de resposta estrogênica presentes na região promotora da enzima luciferase O receptor estrogênico ao ser ocupado por um composto estrogênico agonista ativa a proteína da luciferase, que é induzida pela lise celular na presença do substrato de luciferina e produz luz como sinal mensurável de resposta(LEGLER et al, 1999).Na linha dos bioensaios de leveduras recombinantes, também estão oBMAEREluc/ERα(LESKINEN et al, 2005) e o bioensaio YES (Yeast Estrogen Screen).…”
unclassified